The MoXFo initiative – adherence: Exercise adherence, compliance and sustainability among people with multiple sclerosis: An overview and roadmap for research - Motl, Robert W.; Casey, Blathin; Learmonth, Yvonne Charlotte; Latimer-Cheung, Amy; Kinnett-Hopkins, Dominique L.; Marck, Claudia H.; Carl, Johannes; Pfeifer, Klaus; Riemann-Lorenz, Karin; Heesen, Christoph; Coote, Susan (Multiple sclerosis journal, 2023)
We know very little about exercise adherence, compliance and sustainability in multiple sclerosis (MS), yet adherence is seemingly important for yielding immediate and sustained health benefits. This paper is focused on exercise adherence, compliance and sustainability in the context of informing research and practice involving MS. This focus is critical for clarifying terminology for future research and providing a roadmap guiding clinical research and practice. Our objective was accomplished through a narrative summary of the literature by a panel of experts on exercise adherence from the Moving Exercise Research in Multiple Sclerosis Forward (MoXFo) initiative and a concluding summary of the state of the literature and future research directions. The panel of experts identified three overall themes (Background and Importance; Understanding and Promoting Exercise Adherence, Compliance and Sustainability and Challenges to Exercise Adherence, Compliance and Sustainability) that represented a categorization of nine subthemes. These overall themes and subthemes formed the basis of our recommendations regarding future research broadly involving exercise adherence in MS. Overall, there is limited evidence on rates and determinants of exercise adherence and compliance in MS, and little is known about techniques and interventions for immediate and long-term exercise behaviour change.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Adherence; compliance; exercise; multiple sclerosis; sustainability